Chronic Stress-Related Neural Activity Associates With Subclinical Cardiovascular Disease in a Community-Based Cohort: Data From the Washington, D.C. Cardiovascular Health and Needs Assessment - Powell-Wiley, Tiffany M.; Dey, Amit K.; Rivers, Joshua P.; Chaturvedi, Abhishek; Andrews, Marcus R.; Ceasar, Joniqua N.; Claudel, Sophie E.; Mitchell, Valerie M.; Ayers, Colby; Tamura, Kosuke; Gutierrez-Huerta, Cristhian A.; Teague, Heather L.; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Psychosocial stress correlates with cardiovascular (CV) events; however, associations between physiologic measures of stressors and CVD remain incompletely understood, especially in racial/ethnic minority populations in resource-limited neighborhoods. We examined associations between chronic stress-related neural activity, measured by amygdalar 18Fluorodeoxyglucose (18FDG) uptake, and aortic vascular FDG uptake (arterial inflammation measure) in a community-based cohort. Methods: Forty participants from the Washington, DC CV Health and Needs Assessment (DC-CHNA), a study of a predominantly African-American population in resource-limited urban areas and 25 healthy volunteers underwent detailed phenotyping, including 18FDG PET/CT for assessing amygdalar activity (AmygA), vascular FDG uptake, and hematopoietic (leukopoietic) tissue activity. Mediation analysis was used to test whether the link between AmygA and vascular FDG uptake was mediated by hematopoietic activity. Results: AmygA (1.11 ± 0.09 vs. 1.05 ± 0.09, p = 0.004) and vascular FDG uptake (1.63 ± 0.22 vs. 1.55 ± 0.17, p = 0.05) were greater in the DC-CHNA cohort compared to volunteers. Within the DC-CHNA cohort, AmygA associated with vascular FDG uptake after adjustment for Framingham score and body mass index (β = 0.41, p = 0.015). The AmygA and aortic vascular FDG uptake relationship was in part mediated by splenic (20.2%) and bone marrow (11.8%) activity. Conclusions: AmygA, or chronic stress-related neural activity, associates with subclinical CVD risk in a community-based cohort. This may in part be mediated by the hematopoietic system. Our findings of this hypothesis-generating study are suggestive of a potential relationship between chronic stress-related neural activity and subclinical CVD in an African American community-based population. Taken together, these findings suggest a potential mechanism by which chronic psychosocial stress, such as stressors that can be experienced in adverse social conditions, promotes greater cardiovascular risk amongst resource-limited, community-based populations most impacted by cardiovascular health disparities. However, larger prospective studies examining these findings in other racially and ethnically diverse populations are necessary to confirm and extend these findings.